PENGARUH METODE BERMAIN PERAN TERHADAP KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Sari, Dian Permata Sari Permata; Chairilsyah, Daviq Chairilsyah Daviq; Novianti, Ria Novianti Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is to know of a role-playing method to 5-6 years old children’s interpersonal intelligence in pembina kindergarten pangean distric in kuansing regency. The sample of population in this research is 5-6 years old to amount to 21 person’s. To collect the data is observasion technics. To analysis data used in this research is test-t. The result of research is obtained from the sample results of hypothesis test correlations, with the before and after values of r = 0,718 and the value of significance is 0.000. Because p<0.05 ( 0,718<0.05) then ho rejected. The means of research is role-playing method to 5-6 years old children’s interpersonal intelligence. To receive or reject hypotesis based on SPSS data windows for version 17 then can be seen from a comparison t value and t table is calculation of the test-t, seen that result t value -12,451 from the parties of absolutely price, so the minus (-) price cannot be used (Sugiyono, 2010). Thent value (12,451). DK=40 and the fault stage 5 %=2,021, it can be seen the t price count greater than t table the first fault 5% (12,451>2,021). The mean Ho= were rejected and Ha= accepted. From the research i have conclussion thats the role-playing method is be alternatif to the teacher interpersenol intelligence.Key Words: interpersonal intelligence , role-playing method